FORMULASI YOGHURT SQUEEZE FREEZE-DRIED TAPE KETAN HITAM DAN DAN KACANG ALMOND SEBAGAI ALTERNATIF MAKANAN SELINGAN BAGI PENDERITA DIABETES MELITUS TIPE 2 - Allya Puspalina Nursito; Roro Nur Fauziyah; Agus Sulaeman; Nuniek Widyaningrum; Mona Fitria (Jurnal Gizi dan Dietetik, 2026)
Type 2 Diabetes Mellitus is a chronic metabolic disorder characterized by high blood glucose levels due to insulin resistance. High-fiber and antioxidant food intake such as anthocyanins has been shown to be beneficial in controlling blood glucose levels. Black sticky rice tape and almonds are potential sources of fiber and anthocyanins. Food product innovation in the form of yoghurt squeeze from both ingredients was developed as an alternative functional snack for people with Type 2 DM. This study aims to determine the formulation of freeze-dried black sticky rice tape and almonds on organoleptic properties, anthocyanin levels and fiber. The research design was an experimental study with a Completely Randomized Design (CRD). The research method used a hedonic test to determine organoleptic properties, differential pH for the anthocyanin test and enzymatic gravimetry for the dietary fiber test. The yoghurt squeeze formulation was based on the proportion of freeze-dried black sticky rice tape and almonds 30%:70%; 40%:60%; and 50%:50%. The results of the Kruskal Wallis test showed significant differences in color, taste, texture and overall. The results of organoleptic testing showed that the preferred product was 50%:50%. The results of nutritional analysis showed anthocyanin levels of 5.94 mg/100g and fiber levels of 4.54 grams/100 grams, meeting 181% and 118% of the nutritional adequacy for snacks. Further research is expected to be carried out to determine the effectiveness of freeze-dried yogurt squeeze black sticky rice tape and almonds on samples with Type 2 Diabetes Mellitus.